Ethics and clinical nutrition practice challenge in Covid-19 patients - Dian Permatasari (World Nutrition Journal, 2022)
Covid-19, a disease caused by a novel coronavirus, became a major global human threat that has turned into a pandemic. Pandemics present difficult logistical, medical and ethical challenges to the medical workforce. Pandemics require incorporating public health ethics with clinical ethics.